profitabilitas, likuiditas, ukuran perusahaan dan capital adeuquacy ratio dalam pengaruhnya terhadap kebijakan dividen - Ayik Tritanti; Ika Rosyada Fitriati (Politeknik Ganesha Medan, 2022)
Dividend policy is a decision made by the company on profits earned at the end of each year to be distributed to shareholders in the form of dividends or used as retained earnings to increase capital for investment financing in the future. The company's internal parties and the company's external parties will pay attention to several factors that influence decisions in dividend distribution. The research was conducted with the aim of testing and analyzing the effect of profitability, liquidity, firm size, capital adequacy ratio on dividend policy. The population used in this study are banking companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The use of data in the form of financial reports and annual reports to be used as an alternative to obtain research samples. The research sample was taken using a purposive sampling method with the criteria of companies that have positive profits and companies that distribute dividends during 2015-2020. Based on these criteria, this study obtained a sample of 98 companies. The data analysis technique uses multiple linear regression analysis. The tests that have been carried out have obtained the results that Profitability has a significant negative effect on dividend policy, Liquidity has a significant negative effect on dividend policy, Firm Size has a significant negative effect on dividend policy, Capital Adequacy Ratio has a significant positive effect on dividend policy.